KAJIAN PENGEMBANGAN WISATA BANDAR GRISSEE UNTUK MENYIAPKAN STRATEGI PROMOSI WISATA HERITAGE DI KABUPATEN GRESIK - Rosyada, Amrina; Meirinawati, Meirinawati (Universitas Negeri Surabaya, 2024)
Bandar Grissee has tourism potential in the form of a diversity of historical and cultural heritage in the Old Town Gresik area. This study aims to develop a heritage tourism promotion strategy in Gresik Regency through the development of Bandar Grissee tourism that has been carried out by the Tourism and Creative Economy, Culture, Youth and Sports Office (Disparekrafbudpora). This study examines the strategies applied in the aspects of accessibility, amenity, attractions, and promotion based on the Minister of Tourism Regulation Number 12 of 2020. The research method used is a qualitative approach with narrative analysis techniques which aims to obtain in-depth information based on the views of various subjects involved. Data were collected through documentation, interviews, and observations. The research subjects included the Head of the Tourism Division, Pokdarwis Bandar Grissee, and tourists. The results showed that accessibility to Bandar Grissee is adequate, with facilities and infrastructure that support easy access for tourists. Amenity in this area has been improved to provide more comfort to visitors. Existing attractions, such as historical tours and cultural exhibitions, succeeded in attracting interest and increasing tourist satisfaction. Promotional strategies, including social media campaigns and cooperation with involved stakeholders, have increased visibility and the number of visits. However, this study also identified several obstacles in supporting tourist convenience, such as the lack of directions and public toilets, as well as marketing that has not been optimized. Therefore, suggestions include: 1) Distribute tourist maps and directions, 2) Provide public toilets in Bandar Grissee, 3) Increase the operational schedule of tour buses, and 4) Increase promotion through cooperation with tourism service providers and update virtual tours.